CIRCUIT SIMULATION OF SINGLE FAILURES OF MEMORY MODULES OF ON–BOARD ELECTRONICS - Grichshenko, V.F.; Mukushev, A.A. (Academic Scientific Journal of Computer Science, 2020)
The main objective of the work is the circuit simulation of single failures of a cell of memory modules under given conditions and parameters of transistors of a memory element during the passage of a single particle. The ionization current and critical charges are determined, which lead to a single failure and to the inversion of the logical state of the memory module cell. Application area. The results can be used in the design of microprocessor systems of on-board elecronics of spacecraft.